PENGGUNAANÂ INSTRUCTIONALÂ MATERIALSÂ Â UNTUKÂ MENINGKATKANÂ PEMAHAMANÂ MAHASISWAÂ Â TENTANGÂ SISTEMÂ BAHANÂ BAKARÂ ELECTRONICÂ FUELÂ INJECTIONÂ Â (Jurnal Pendidikan Teknik Mesin, 2008)
Penelitian ini bertujuan untuk menyusun Â Instructional Â Materials Â dan meningkatkan pemahamanÂ mahasiswa Â tentang penggunaannya pada Â sistem Electronic Fuel Â injection pada mata kuliah Perakitan otomotif Â II.Â Desain penelitian adalah quasi experiment dengan pre dan pos Â tes. Populasi penelitian adalah mahasiswa TeknikÂ Mesin Unnes yang mengikuti mata kuliah Perakitan otomotif Â II yaitu Â sejumlah 42 orang yang Â terbagi dalam duaÂ kelompok. Hasil penelitian menunjukkan adanya peningkatan pemahaman mahasiswa tentang sistem vahan bakarÂ EFI setelah menggunakan Instructional Materials. Hasil belajar rataâ€rata pre tes Â adalah 60,92 dan rataâ€rata pos tesÂ adalah 77,83. Dengan demikian terjadi peningkatan hasil belajar belajar sebesar 27,77% jika dibandingkan denganÂ sebelum menggunakan Instructional Materials pada sistem bahan bakar EFI.Â This Â research Â aims Â to Â create Â Instructional materials Â and Â to Â increase Â students Â understanding of Â lessonÂ about Â the Â use Â instructional Â materials Â and Â the Â fuel Â system Â Electronic Â Fuel Â Injection Â (EFI) Â in Â the Â AutomotiveÂ Assembly II lecture, Mechanical Engineering students of State University of Semarang in 2009/2010. Â The researchÂ used a quasiâ€experimental design; it is preÂtestÂpostÂtest design. The population of this research was students whoÂ took Â the Â Automotive Â Assembly Â II Â lecture, Â Mechanical Â Engineering Â Department, Â Semarang Â State Â UniversityÂ consisting of 42 students in two different group. Because there was only one class for this lecture, all students fromÂ the class were chosen to be population. The result of analyzed data is that there is improvement in the fuel systemÂ Electronic Fuel Injection (EFI) understanding after the use of Â the instructional materials for Automotive AssemblyÂ II lecture. The average value before using instructional materials (preâ€test) was 60.92 and the average value afterÂ using Â instructional Â materials Â (postâ€test) Â was Â 77.83. Â Therefore, it can be stated that the use of instructionalÂ materials EFI fuel system has been well and effective in accordance with studentsâ€™ achievements. The achievementsÂ mentioned Â here Â are Â the Â achievements Â of Â students who Â joined Â the Â Assembly Automotive Â II Â lecture Â in which Â theÂ achievements Â value Â was Â improved Â from Â 27.77%; Â the Â percentage Â before Â using Â instructional Â materials Â EFI Â fuelÂ system.Keywords: instructional materials, electronic fuel injection (EFI)